Isolation, purification and characterization of vinblastine and vincristine from endophytic fungus fusarium oxysporum isolated from catharanthus roseus - Kumar, Ashutosh; Patil, Deepak; Rajamohanan, Pattuparambil Ramanpillai; Ahmad, Absar (Plos One, 2013)
Endophytic fungi reside in a symbiotic fashion inside their host plants, mimic their chemistry and interestingly, produce the same natural products as their hosts and are thus being screened for the production of valuable compounds like taxol, camptothecin, podophyllotoxin, etc. Vinblastine and vincristine are excellent anti-cancer drugs but their current production using plants is non-abundant and expensive. In order to make these drugs readily available to the patients at affordable prices, we isolated the endophytic fungi from Catharanthus roseus plant and found a fungus AA-CRL-6 which produces vinblastine and vincristine in appreciable amounts. These drugs were purified by TLC and HPLC and characterized using UV-Vis spectroscopy, ESI-MS, MS/MS and H-1 NMR. One liter of culture filtrate yielded 76 mu g and 67 mu g of vinblastine and vincristine respectively. This endophytic fungal strain was identified as Fusarium oxysporum based upon its cultural and morphological characteristics and internal transcribed spacer (ITS) sequence analysis.

Prediction of bioactive compounds using computed NMR chemical shifts - Karthikeyan, Muthukumarasamy; Rajamohanan, Pattuparambil Ramanpillai; Vyas, Renu (Combinatorial Chemistry & High Throughput Screening, 2015)
NMR based chemical shifts are an important diagnostic parameter for structure elucidation as they capture rich information related to conformational, electronic and stereochemical arrangement of functional groups in a molecule which is responsible for its activity towards any biological target. The present work discusses the importance of computing NMR chemical shifts from molecular structures. The NMR chemical shift data (experimental or computed) was used to generate fingerprints in binary formats for mapping molecular fragments (as descriptors) and correlating with the bioactivity classes. For this study, chemical shift data derived binary fingerprints were computed for 149 classes and 4800 bioactive molecules. The sensitivity and selectivity of fingerprints in discriminating molecules belonging to different therapeutic categories was assessed using a LibSVM based classifier. An accuracy of 82% for proton and 94% for carbon NMR fingerprints were obtained for anti-psoriatic and anti-psychotic molecules demonstrating the effectiveness of this approach for virtual screening.
Keywords: Chemical shift; fingerprints; NMR; similarity searching; virtual screening

Template determines whether chemically identical nanoparticle scaffolds show elastic recovery or plastic failure - Suresh, Karthika; Patil, Shivprasad; Rajamohanan, Pattuparambil Ramanpillai; Kumaraswamy, Guruswamy (Langmuir, 2016)
Subtle variations in the preparation of ice-templated nanoparticle assemblies yield monoliths that are chemically identical but exhibit qualitatively different mechanical behavior. We ice template aqueous dispersions to prepare macroporous monoliths largely comprising silica nanoparticles held together by a crosslinked polymer mesh. When the polymer is crosslinked in the presence of ice crystals, we obtain an elastic sponge that is capable of recovery after imposition of large compressive strains (up to 80%). If, however, the ice is lyophilized before the polymer is crosslinked, we obtain a plastic monolith that fails even for modest strains (less than 10%). The elastic sponge and the plastic monolith are chemically identical; they have the same organic content, the same ratio of polymer to crosslinker, and the same average crosslink density. Atomic force microscopy (AFM) was used to probe the local mechanical properties of the crosslinked polymer mesh. These measurements indicate that plastic monoliths dissipate significantly more energy and have a larger spatial variation in local mechanical response relative to the elastic sponges. We believe that this behavior might correlate with a wider spatial distribution of crosslinks in plastic scaffolds relative to elastic scaffolds.

Optimization for the production of mycelial biomass from Benjaminiella poitrasii to isolate highly deacetylated chitosan - Mane, S. R.; Pathan, Ejaj K.; Kale, D.; Ghormade, Vandana; Gadre, Ramchandra V.; Rajamohanan, Pattuparambil Ramanpillai; Badiger, Manohar V.; Deshpande, Mukund V. (Journal of Polymer Materials, 2017)
Benjaminiella poitrasii, a dimorphic zygomycetous fungus contains more chitosan in the mycelial cell wall than the cell wall of its yeast form. The optimized medium containing yeast extract, peptone, MgSO4, KH2PO4, trace metals (Fe2+, Mn2+ Zn2+ and Co2+ ) solution and 1% starch produced 10-12 g/L(dry wt.) of mycelial biomass in 48 h in a 2L fermenter. Using 1N NaOH treatment from 1 g of dried biomass 51.00 ± 0.52 mg of chitosan of 42.82 KDa molecular weight and 94.24 % degree of deacetylation was extracted. With Metarhizium anisopliae chitin deacetylase (CDA), chitosan yield was 59.00 ± 0.84 mg while treatment with CDA of B. poitrasii it was 78.05 ± 0.58 mg/g of dry wt. of biomass. The chitosan dissolved in 2% acetic acid showed higher antifungal activity against Candida albicans (MIC90 0.025 mg/mL) and Candida glabrata (MIC90 0.2 mg/mL) than chitosan extracted from marine source (MIC90 >1.6 mg/mL) suggesting use of fungal chitosan in healthcare.

Investigation of domain structures in monomethoxy poly(ethylene glycol)-b-poly(caprolactone) grafted poly(acrylic acid) by NMR diffusion studies - Tiwari, Neha; Badiger, Manohar Virupax; Rajamohanan, Pattuparambil Ramanpillai; Ravindranathan, Sapna (Polymer International, 2022)
Associating polymers developed by grafting a block copolymer of monomethoxy poly(ethylene glycol)-b-poly(caprolactone) (MPEG-b-PCL) onto poly(acrylic acid) undergo an irreversible sol-gel transition on heating. The influence of various physicochemical parameters on the thermoresponsive behaviour was examined by rheology and NMR studies. Pulsed field gradient NMR diffusion studies were performed to probe the mechanism of thermally induced gelation. Analysis of the diffusion data reveals the presence of loosely and strongly associated structures which respond differently to variation in temperature. It is observed that the polymer solution, which is visibly homogeneous, is heterogeneous on a mesoscopic scale with a distribution of domains. Detailed investigation of the thermally induced sol-gel transition shows that the mechanism of gelation involves irreversible alterations in the domain structure and size. (c) 2022 Society of Industrial Chemistry.
Keywords: associating polymers; hydrophobically modified polymers; NMR diffusion studies; Rheology; sol-gel transition; thermoresponsive polymers